COW URINE INFLUENCE THE GROWTH OF LOOSELEAF LETTUCE SEEDLINGS IN THE SOUTHWEST OF PARANÁ? - Marangon, Ricardo Júnior; Dotto, Marcelo; Remor Lopes, Allan; Moreno Giarola, Camila; Pirola, Kelli (Revista Brasileira de Engenharia de Biossistemas, 2021)
The use of cow urine can be considered an agricultural practice of low cost for farmers in Southwest Paraná. This work aimed to evaluate the effect of cow urine on growth and production of lettuce seedlings. The experimental design was completely randomized with four replications. We analyzed the effects of seven cow urine concentrations (1,0, 2,0, 3,0, 4,0, 5,0, 6,0 and 7,0%) (v v-1). In the conditions of Southwest Paraná, the best lettuce development was obtained with the application of 5,0% concentration. Chlorophyll indices (a and b), were also higher with the use of concentration 5,0% concentration.